[Nle4, D-Phe7]-MSH Inhibits Toll-Like Receptor (TLR)2- and TLR4-Induced Microglial Activation and Promotes a M2-Like Phenotype - Carniglia, Lila (2016)
α-melanocyte stimulating hormone (α-MSH) is an anti-inflammatory peptide, proved to be beneficial in many neuroinflammatory disorders acting through melanocortin receptor 4 (MC4R). We previously determined that rat microglial cells express MC4R and that NDP-MSH, an analog of α-MSH, induces PPAR-γ expression and IL-10 release in these cells. Given the great importance of modulation of glial activation in neuroinflammatory disorders, we tested the ability of NDP-MSH to shape microglial phenotype and to modulate Toll-like receptor (TLR)-mediated inflammatory responses. Primary rat cultured microglia were stimulated with NDP-MSH followed by the TLR2 agonist Pam3CSK4 or the TLR4 agonist LPS. NDP-MSH alone induced expression of the M2a/M2c marker Ag1 and reduced expression of the M2b marker Il-4rα and of the LPS receptor Tlr4. Nuclear translocation of NF-κB subunits p65 and c-Rel was induced by LPS and these effects were partially prevented by NDP-MSH. NDP-MSH reduced LPS- and Pam3CSK4-induced TNF-α release but did not affect TLR-induced IL-10 release. Also, NDP-MSH inhibited TLR2-induced HMGB1 translocation from nucleus to cytoplasm and TLR2-induced phagocytic activity. Our data show that NDP-MSH inhibits TLR2- and TLR4-mediated proinflammatory mechanisms and promotes microglial M2-like polarization, supporting melanocortins as useful tools for shaping microglial activation towards an alternative immunomodulatory phenotypE